Tlx3 Function in the Dorsal Root Ganglion is Pivotal to Itch and Pain Sensations - Huang, Chengcheng; Lu, Fumin; Li, Ping; Cao, Cheng; Liu, Zijing (Frontiers in Molecular Neuroscience, 2017)
Itch, a sensation eliciting a desire to scratch, is distinct from but not completely independent of pain. Inspiring achievements have been made in the characterization of itch-related receptors and neurotransmitters, but the molecular mechanisms controlling the development of pruriceptors remain poorly understood. Here, our RNAseq and in situ hybridization data show that the transcription factor Tlx3 is required for the expression of a majority of itch-related molecules in the dorsal root ganglion (DRG). As a result, Tlx3F/F;Nav1.8-cre mice exhibit significantly attenuated acute and dry skin-induced chronic itch. Furthermore, our study indicates that TRPV1 plays a pivotal role in the chronic itch evoked by dry skin and allergic contact dermatitis. The mutants also display impaired response to cold and inflammatory pain and elevated response to capsaicin, whereas the responses to acute mechanical、 thermal stimuli and neuropathic pain remain normal. In Tlx3F/F;Nav1.8-cre mice, TRPV1 is derepressed and expands predominantly into IB4+ non-peptidergic neurons. Collectively, our data reveal a molecular mechanism in regulating the development of pruriceptors and controlling itch and pain sensations.